An update on self-regulation in the Canadian securities industry (2009-2016): Funnel in, funnel out and funnel away. Issue 3 (8th July 2019) - Lokanan, Mark
Abstract : Purpose: This paper aims to analyze the processing of complaints against investment advisors and Member firms through the Investment Industry Regulatory Organization of Canada (IIROC) enforcement system between 2009 and 2016. The paper used the misconduct funnel to show the number of complaints that are "funneled in, " and how these complaints are subsequently "funneled out" and "funneled away" at the investigation and prosecution stages of IIROC enforcement system. Design/methodology/approach: The paper uses data from IIROC enforcement annual reports from 2009 to 2016. A combination of descriptive statistics and correlation matrices was used to analyze the data. Findings: The findings indicate that while IIROC "funneled in" more complaints, a significant proportion of complaints were "funneled out" of its enforcement system and funneled "away" from the criminal justice system. Fines imposed were often not collected from individual offenders. IIROC, it seems, is ineffective in handling the more serious and systematic industry problems. Practical implications: It is hard not to see the findings from this study being used by the provincial securities commissions and the federal government to support the call for a national securities regulator in Canada. Originality/value: This is the first study of its kind to systematically analyze the enforcement performance of IIROC.